101 National Trends in Emergency Department Ondansetron Use and Clinical Outcomes Among Children with Acute Gastroenteritis. (29th October 2021) - Rogers, Sarah; Freedman, Stephen; Klassen, Terry; Burstein, Brett
Abstract: Primary Subject area: Emergency Medicine - Paediatric Background: Acute gastroenteritis (AGE) is among the most common illnesses for which children are evaluated in the Emergency Department (ED). Among children with AGE, ondansetron has been shown to reduce vomiting, intravenous (IV) fluid administration and hospitalizations when administered in the ED. Objectives: To determine whether increasing ondansetron administration is associated with a concomitant decline in IV rehydration and hospitalization among children presenting with AGE in a broad, nationally representative ED sample. Design/Methods: This was a cross-sectional analysis of the US Centers for Disease Control and Prevention (CDC) National Hospital Ambulatory Medical Care Survey (NHAMCS) database from 2006 to 2015. Children < 18 years old with a discharge diagnosis of AGE were included for analysis. Survey weighting procedures were applied to generate population-level estimates and to perform multivariable logistic regression to identify factors associated with ondansetron administration. Results: There were an estimated 15.1 million (95% CI 13.5-16.7) visits for AGE during the 10-year study period. AGE visits increased as a proportion of all pediatric ED visits over time (4.6% in 2006, 5.7% in 2015; p-trend=0.013). The mean patient age was 4.7 (95% CI 4.5-5.0) years, and most visits were to non-teaching (86.6%, 95% CI 83.3-89.3%) and non-pediatric (83.4%, 95% CI 78.2-87.5%) hospitals. The proportion of patients receiving ondansetron increased over time (11.8% in 2006, 62.5% in 2015; p-trend < 0 .001), both in the ED (10.6% in 2006, 55.5% in 2015; p-trend < 0 .001) and as outpatient prescriptions (3.3% in 2006, 45.3% in 2015; p-trend < 0 .001). Over the same period, there was no change in hospitalizations (2.9% overall, 95% CI 2.2-3.7%; p-trend=0.144). IV hydration for AGE decreased (31.8% in 2006, 24.9% in 2015; p-trend < 0 .048), as did IV fluid administration across all other pediatric ED visits (10.3% in 2006, 7.8% in 2015; p-trend < 0 .023). After adjustment for patient- and hospital-level factors, the odds ratio for IV rehydration among children with AGE was 0.97 (95% CI 0.92-1.01). Multivariable analysis found younger age (aOR 0.94, 95% CI 1.04-1.09), Medicaid/Medicare insurance (aOR 0.74; 95% CI 0.57-0.97), and presentation to a teaching hospital (aOR 0.74; 95% CI 0.54-0.99) were inversely associated with ondansetron administration. Other antiemetics most commonly used were promethazine (7.4%, 95% CI 5.9-9.2%), metoclopramide (1.8%, 95% CI 1.3-2.5%) and trimethobenzamide (1.5%, 95% CI 1.1-2.1%). Antimotility agents, H2-receptor blockers, and probiotics were infrequently used. Conclusion: Both ED and outpatient prescribing of ondansetron for children with AGE increased; however, no concomitant decline was observed in hospitalizations or IV rehydration. Guidelines and quality improvement efforts are needed to target ondansetron administration to children most likely to benefit to minimize adverse events and costs associated with overuse.